2010
DOI: 10.1007/s10531-010-9778-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of pollution on marine life in Southeast Asia

Abstract: Pollutants, originating from both land and sea, are responsible for significant lethal and sub-lethal effects on marine life. Pollution impacts all trophic levels, from primary producers to apex predators, and thus interferes with the structure of marine communities and consequently ecosystem functioning. Here we review the effects of sediments, eutrophication, toxics and marine litter. All are presently major concerns in Southeast Asia (SE Asia) and there is little indication that the situation is improving. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(68 citation statements)
references
References 126 publications
0
67
0
1
Order By: Relevance
“…Human activities in the coastal seascape can physically damage seagrass beds via coastal construction, boat movement, anchor damage and de-ballasting (Burkholder et al 2007, Todd et al 2010. Seagrass beds are susceptible to reduced light availability (Ralph et al 2007, van der Heide et al 2007 and to increases in nutrient concentrations and toxins (Orth et al 2006, Freeman et al 2008, Todd et al 2010.…”
Section: Seagrass Bedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human activities in the coastal seascape can physically damage seagrass beds via coastal construction, boat movement, anchor damage and de-ballasting (Burkholder et al 2007, Todd et al 2010. Seagrass beds are susceptible to reduced light availability (Ralph et al 2007, van der Heide et al 2007 and to increases in nutrient concentrations and toxins (Orth et al 2006, Freeman et al 2008, Todd et al 2010.…”
Section: Seagrass Bedsmentioning
confidence: 99%
“…Seagrass beds are susceptible to reduced light availability (Ralph et al 2007, van der Heide et al 2007 and to increases in nutrient concentrations and toxins (Orth et al 2006, Freeman et al 2008, Todd et al 2010. Loss of seagrass beds has been associated with changes in neighbouring ecosystems.…”
Section: Seagrass Bedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment-bound heavy metals have a tendency to adsorb and accumulate on finegrained particles that eventually move into the depositional areas (Zhang et al, 2001;Morillo et al, 2002;Jain, 2004;Man et al, 2004;Qiu et al, 2005;Singh et al, 2005;Mendiguchía et al, 2006). Sediment pollution by heavy metals has been regarded as a critical problem in marine environment because of their toxicity and bioaccumulation (Chapman et al, 1998;Islam and Tanaka, 2004;Singh et al, 2005;Todd et al, 2010). Many studies have shown that heavy metals in sediments could significantly impact the health of marine ecosystem (Snodgrass et al, 2008;Zheng et al, 2008;Besser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al, 2001), there is clearly a long way to go. Although yet to be adequately quantified at a global scale, marine debris loads are likely to be highest in the coastal environments of developing countries (Todd et al, 2010), many of which are in the most biodiverse regions of the planet (Roberts et al, 2002). Marine debris is thus one of the many threats that leads to an overrepresentation of marine biodiversity hotspots (areas of high endemicity and diversity that are also at high risk) in the coral triangle of South-east Asia/Western Pacific.…”
Section: Introductionmentioning
confidence: 99%